Artemin promotes proliferation and metastasis in human laryngeal squamous cell carcinoma - Gao, Chao-Bing (Int J Clin Exp Pathol, 2017)
Laryngeal squamous cell carcinoma (LSCC) is the main type of human laryngeal cancer which is one of the most common malignant head and neck tumors and the outcomes of LSCC patients are always poor. The intrinsic molecular mechanisms in initiation, development, growth and metastasis of LSCC remain unclear. Further researches are necessary and urgent. In this article, we examined artemin (ARTN) promoted both cell proliferation and metastasis of human LSCC cells Hep-2 by siRNA mediated ARTN knocking down using MTT assay, cell migration assay and cell invasion assay. Moreover, we examined the expression level of ARTN in LSCC tissues was much higher than that in benign laryngeal polyp tissues. In addition, ARTN was identified as a direct target of miR-223 and miR-223 suppressed the expression of ARTN in LSCC cells. Supplement to our former study, we demonstrated ARTN was oncogenic both in vitro and in clinical tissues. As a result, ARTN could be used as a potential therapeutic target for human LSCC.